Oral Charcoal Adsorbents Attenuate Neointima Formation of Arteriovenous Fistulas - Yu-Chung Shih; Chih-Cheng Wu; Shen-Chih Wang; Jun-Yang Liou; Po-Hsun Huang; Der-Cherng Tarng (Toxins, 2020)
Chronic kidney disease (CKD) accelerates the development of neointima formation at the anastomosis site of arteriovenous (AV) fistulas. Accumulation of certain uremic toxins has a deleterious effect on the cardiovascular system. The oral charcoal adsorbent, AST-120, reduces circulating and tissue uremic toxins, but its effect on neointima formation at an AV fistula is unknown. To understand the effect of CKD and AST-120 on neointima formation, we created AV fistulas (common carotid artery to the external jugular vein in an end-to-side anastomosis) in mice with and without CKD. AST-120 was administered in chow before and after AV fistula creation. Administration of AST-120 significantly decreased serum indoxyl sulfate levels in CKD mice. CKD mice had a larger neointima area than non-CKD mice, and administration of AST-120 in CKD mice attenuated neointima formation. Both smooth muscle cell and fibrin components were increased in CKD mice, and AST-120 decreased both. RNA expression of MMP-2, MMP-9, TNFα, and TGFβ was increased in neointima tissue of CKD mice, and AST-120 administration neutralized the expression. Our results provided in vivo evidence to support the role of uremic toxin-binding therapy on the prevention of neointima formation. Peri-operative AST-120 administration deserves further investigation as a potential therapy to improve AV fistula patency.